Anti-crisis program to minimize risks of psychological security of educational environment at the professional educational organization - Denisova Y. M., Biserinkina L. K., Leongardt O. R. (Relevant lines of scientific research: development prospects, 2017)
the article presents anti-crisis program to minimize risks of psychological security of educational environment at the professional educational organization. The authors justify the relevance of this question for educational institution of the system of professional education. They also give the results of the study of assessing the psychological safety of the educational environment (I.A. Baeva’s questionnaire) on the example of a group of students according to the main diagnostic indicators (attitude toward the educational environment, the essential characteristics of the educational environment and their satisfaction and protection from psychological violence during interaction). The risks and threats to the safety of the educational environment have been identified. The authors have developed the plan on the minimization, which defines types of assistance, personal responsibility, time frame and evaluation criteria. The planned results of approbation of the anti-crisis program within the framework of the professional educational organization have been formulated.
Keywords: среднее профессиональное образование; образовательная среда; антикризисная программа; educational environment; secondary vocational education; anti-crisis program